If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) + 5x = 59 Reorder the terms: 3(1 + x) + 5x = 59 (1 * 3 + x * 3) + 5x = 59 (3 + 3x) + 5x = 59 Combine like terms: 3x + 5x = 8x 3 + 8x = 59 Solving 3 + 8x = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8x = 59 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = 59 + -3 8x = 59 + -3 Combine like terms: 59 + -3 = 56 8x = 56 Divide each side by '8'. x = 7 Simplifying x = 7
| 10+3r-7-6(9-3)(3-5r)+9r/3 | | t^2-7=0 | | |x-1|=5x+10 | | 7(d-5)+8=(3d-5)+1 | | -x-13=45 | | 3-4x/1+5x=1/2+3x | | 8n-2=-9+7n | | y=4x+42 | | 7/x+3=-14/x-3 | | 5(2x-4)+5x=3(x+3)-15 | | 5(n+4)+6n=97 | | 6r^2-3r-2=0 | | 4x+1=220 | | -3+10y+6=15+12y-8 | | 15-4*3+2= | | -7x+4(-3x+7)=-105 | | d^2-7d-7=0 | | -4X+10=65+X | | 5x+6=5x-6 | | 6-4(2x+3)-x=-73 | | n^2=100 | | 2y-4=7y+7 | | 9[3-(2-x)]+6x=3(5x+5)-6 | | 2y-4=7x+7 | | -s^2-6s=0 | | 3x+18=-3 | | -[9z-(19z+1)]=1+(9z+7) | | 10x+5=2x+4 | | k/4+2=6 | | -m^2+m=0 | | 2a+7=-5a+28 | | -3-5=11-7x |